Transformative Learning and the Ecological Crisis: Insights from The Tao of Liberation - Mark Hathaway (Adult Education Research Conference, 2011)
The complexity and scale of the ecological crisis poses unique challenges to transformative learning. To address these, The Tao of Liberation (Hathaway & Boff, 2009) offers insights to reconceptualize transformative learning from an ecological perspective, including new ways of framing learning goals, the nature of liberation, and the process of worldviews transformation. The Tao also provides analysis addressing some of the key psychological obstacles impeding transformative learning related to the ecological crisis. Finally, The Tao outlines four “paths to liberation” that suggest concrete processes that can foster integral transformative learning.
Keywords: transformative learning; environmental education; worldviews